Long-term channelrhodopsin-2 (ChR2) expression can induce abnormal axonal morphology and targeting in cerebral cortex - Miyashita, Toshio; Shao, Yu R.; Chung, Jason; Pourzia, Olivia; Feldman, Dan (Frontiers in Neural Circuits, 2013)
Long-term expression of optogenetic proteins including channelrhodopsin-2 (ChR2) is widely used to study neural circuit function, but whether ChR2 expression itself perturbs circuits is not known. We expressed a common construct, CAG::ChR2(H134R)-EYFP-WPRE, in L2/3 pyramidal cells in rat somatosensory cortex via in utero DNA electroporation. L2/3 pyramidal cells expressed ChR2-EYFP, but histology revealed abnormal morphology and targeting of ChR2-EYFP expressing axons, beginning at postnatal day (P) 33 and increasing with age. Axonal abnormalities included cylinders that enveloped pyramidal cell proximal apical dendrites, and spherical, calyx-like structures that surrounded neuronal cell bodies, including in L4. These are abnormal subcellular and laminar targets for L2/3 pyramidal cell synapses. Abnormalities did not occur in cells expressing GFP instead of ChR2, or in intermixed ChR2-negative axons. Long-term viral-mediated expression (80 d) did not cause axonal abnormalities when the CAG promoter was used, but produced some abnormalities with the stronger αCaMKII promoter (albeit much less than with in utero electroporation). Thus, under some circumstances high-level, long-term expression of ChR2-EYFP can perturb the structural organization of cortical circuits.